Evaluation of Price Adjustment Coefficient for Construction Contracts - A. K. Mishra; Navneet Chaudhary; P. S. Aithal, (International Journal of Management, Technology and Social Sciences (IJMTS), 2023)
Purpose: There are many bridges being constructed in Nepal. Brides of different types like Bailey truss, cable stayed, RCC Arch, pre-stressed, RCC Slab, RCC T-Beam, Steel truss, RCC Box, Stone masonry arch, suspension, and suspended bridges are being tendered and constructed at present in Nepal. Most of the bridges being constructed are of RCC T-beam and Prestressed bridges. It has been found the need to carry out research to develop logical price adjustment coefficient ranges for RCC T-beam and Prestressed bridges contracts to make the price adjustment provision more uniform. Design/Methodology/Approach: Primary data was collected by office visits, constituting focus group discussions and interviews of the beneficiaries (clients & contractors) and the secondary data was collected through the Interim payment certificates and contract documents of the selected bridge. Price adjustment calculation was done and price adjustment coefficient ranges for RCC T-girder and prestressed concrete bridges were fixed. Findings/Result: Price adjustment coefficients (Labour coefficient, Material coefficient & Equipment coefficient) were found significantly different since their corresponding weightage in bridge construction are different. Thus, different ranges are to be adopted as per their weightage which is justified by this ANOVA Test. If price adjustment coefficient ranges are not provided in the bidding document, it was seen that the contractor tried to manipulate price adjustment provision to his/her benefit. Originality/Value: The necessary ranges have been developed for coefficients of price adjustments to provide a guideline to the contractor in bidding price adjustment coefficients Paper Type: Research paper